Digitization of journal collections in libraries: a case study of Kenneth Dike Library, University of Ibadan, Nigeria (2013)
Digitization of journal collections in libraries is inevitable with the advent of Information Communication Technology (ICT). There is a need to digitize journals in the academic library in order to preserve and to give wider visibility and accessibility to information resources for teaching, learning, and research. This article describes the processes of journal collection digitization in Kenneth Dike Library, University of Ibadan. Underfunding and copyright clearance are the challenges encountered, among others. The study recommends adequate funding and concludes that the benefit of instant access to digital information is the most distinguishing attribute in this present information age.